The human cytomegalovirus US6 glycoprotein inhibits transporter associated with antigen processing-dependent peptide translocation - Lehner, Paul J. (The National Academy of Sciences of the USA, 1997)
In its attempt to evade cytotoxic T cell recognition, human cytomegalovirus encodes several genes that target MHC class I molecules at different points in their assembly pathway. We show here that the human cytomegalovirus US6 gene encodes a 22-kDa glycoprotein that binds the transporter-associated with antigen processing (TAP)/class I complex and inhibits translocation of peptide from the cytosol to the endoplasmic reticulum. Major histocompatibility complex class I molecules are therefore unable to load TAP-dependent peptides, resulting in the retention of MHC class I molecules in the endoplasmic reticulum, with a consequent reduction in class I at the cell surface. Interferon-γ treatment of US6 transfected cells overcomes this inhibition of peptide translocation and restores class I at the cell surface to wild type levels. The functional consequence of TAP inhibition is that US6 transfected cells are unable to present endogenous antigen to cytotoxic T lymphocytes and are therefore resistant to cytotoxic T lymphocyte lysis.